Green Campus and Ecological Citizenship: The Mediating Role of Energy Citizenship - Nugroho Dwi Saputra; Edi Suhartono (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze the influence of the implementation of UM Green Campus program on students’ ecological citizenship awareness at Universitas Negeri Malang, with energy citizenship as a mediating variable. The research uses a quantitative approach with a descriptive-explanatory design. Data were collected using a Likert-scale questionnaire distributed to 415 respondents selected through proportional random sampling. Data analysis employed a path analysis model using SEM-PLS method. The results show that the direct effect of Green Campus implementation on ecological citizenship awareness is not statistically significant, with a T-statistic value of 1.308 and a P-value of 0.191 (> 0.05). However, the effect of energy citizenship on ecological citizenship is significant, as indicated by a T-statistic of 17.224 and a P-value of 0.000. Furthermore, the indirect influence of Green Campus implementation on ecological citizenship through energy citizenship is also significant (T-statistic of 15.347; P-value of 0.000). These findings suggest that the success of Green Campus implementation in increasing ecological citizenship depends on how well energy citizenship values are internalized. This research highlights the importance of participatory and educational efforts in promoting energy citizenship to encourage students’ active involvement in sustainable environmental transformation.